Konsentrasi, Dehidrasi Setelah Latihan Bertahan Pada Permainan Sepak Bola - Ahmad Atiq; Witri Suwanto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2023)
This study has the objective of knowing the status of concentration, dehydration after endurance training in soccer games. The specific target of this research is to help provide information and knowledge to athletes and coaches in preparing athletes' performance in paying attention to athlete's fluid consumption in each training concentration and performance in training, competing. This study used a quantitative descriptive method with survey techniques with the results of the research. The results showed that the average male athlete had a concentration of 10 in the good category with a percentage of 43%, in the medium category there were 7 players with a percentage of 30% and in the sufficient category there were 6 athletes, there were 26%. dehydration of 23 athletes as many as 8 people (17.30%) had good hydration status, 8 people (34.60%) had moderate dehydration status, 5 people (39.2%) had dehydration status and 2 people (8.7% ) have a severely dehydrated status. The conclusion of the research is the status of dehydration after doing man to man exercises is very dehydrated as much as 39.2% and dehydrated as much as 34.80%. Keywords : Concentration, Dehydration, Football, Survival Training,